La gestión financiera y su relación con el desarrollo organizacional de la empresa AF Boullosa de la ciudad de Iquitos, periodo 2023 - Mosquera Chanchari, Barbara de Fatima (2023)
Financial management is vital in the growth and economic development of the company, because management is all those actions that are oriented in the efficient use of financial resources with the aim of obtaining the greatest possible profitability; for its part, organizational development involves a number of factors that senior management should implement so that staff can achieve better performance and at the same time increase their productivity for the benefit of the entity. The research is entitled "Financial Management and its relationship with the organizational development of the company AF Boullosa of the city of Iquitos, period 2023", aims to determine the relationship between financial management and organizational development. The study corresponded to a quantitative type and correlative descriptive design, using the survey as a technique and the questionnaire as an instrument, its reliability has been determined by the reliability test and applied to a sample represented by 35 individuals. The results indicate that there is a moderate positive relationship according to the Pearson correlation coefficient calculated at 0.585 and a degree of significance 0.000.